2018
DOI: 10.1002/biot.201800306
|View full text |Cite
|
Sign up to set email alerts
|

Cell Seeding on UV‐C‐Treated 3D Polymeric Templates Allows for Cost‐Effective Production of Small‐Caliber Tissue‐Engineered Blood Vessels

Abstract: There is a strong clinical need to develop small‐caliber tissue‐engineered blood vessels for arterial bypass surgeries. Such substitutes can be engineered using the self‐assembly approach in which cells produce their own extracellular matrix (ECM), creating a robust vessel without exogenous material. However, this approach is currently limited to the production of flat sheets that need to be further rolled into the final desired tubular shape. In this study, human fibroblasts and smooth muscle cells were seede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…This study was approved by the ethical research board of the CHU de Québec (Protocol number: 1115C & 1115D) and individuals were recruited on a voluntary basis following informed consent. Immortalized human cerebral microvascular endothelial cells (hCMEC/D3) were purchased from Cedarlane Laboratories, human microvascular endothelial cells were obtained from foreskin dermis as described previously, 18 human umbilical vein endothelial cells were isolated from a human umbilical cord vein, 19 human fibroblasts were isolated following breast surgery, 1,9 and smooth muscle cells were isolated from a human umbilical cord vein. 19 Cells were grown in an incubator at 37 °C, 8% CO 2 and 95% relative humidity, and the culture medium was changed 3 times a week.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study was approved by the ethical research board of the CHU de Québec (Protocol number: 1115C & 1115D) and individuals were recruited on a voluntary basis following informed consent. Immortalized human cerebral microvascular endothelial cells (hCMEC/D3) were purchased from Cedarlane Laboratories, human microvascular endothelial cells were obtained from foreskin dermis as described previously, 18 human umbilical vein endothelial cells were isolated from a human umbilical cord vein, 19 human fibroblasts were isolated following breast surgery, 1,9 and smooth muscle cells were isolated from a human umbilical cord vein. 19 Cells were grown in an incubator at 37 °C, 8% CO 2 and 95% relative humidity, and the culture medium was changed 3 times a week.…”
Section: Methodsmentioning
confidence: 99%
“…Immortalized human cerebral microvascular endothelial cells (hCMEC/D3) were purchased from Cedarlane Laboratories, human microvascular endothelial cells were obtained from foreskin dermis as described previously, 18 human umbilical vein endothelial cells were isolated from a human umbilical cord vein, 19 human fibroblasts were isolated following breast surgery, 1,9 and smooth muscle cells were isolated from a human umbilical cord vein. 19 Cells were grown in an incubator at 37 °C, 8% CO 2 and 95% relative humidity, and the culture medium was changed 3 times a week. We also conducted experiments with hCMEC/D3 at a maximum passage of 35 to avoid genetic instability and endothelial cell markers loss.…”
Section: Cell Culturementioning
confidence: 99%
“…However, it could prove interesting as it has demonstrated its potential to produce well-organized epithelia when cells from the organ to be reconstructed are used. Moreover, this technique seems particularly suitable for reconstructing the esophagus, which presents essential similarities to those which have already been rebuilt [49,226,227]. This strategy is also interesting because it has demonstrated a strong potential to be prevascularized and thus allows rapid reconnection of the network of the graft to that of the host [228][229][230].…”
Section: Tissue Engineeringmentioning
confidence: 99%
“…These cell sheets can be superimposed to generate thicker and planar mesenchymal tissue that can be cultured for several weeks. The self-assembly approach allows the reconstruction of tissues that are histologically and physiologically similar to their in vivo counterparts [91]. This method has been successfully used to reconstruct numerous human tissues such as blood vessels [91,92], bilayered skin [3], bladder [93], adipose tissue [94], heart valve [95], ureter [96], and cornea [97].…”
Section: The Self-assembly Approach Of Tissue Engineeringmentioning
confidence: 99%
“…The self-assembly approach allows the reconstruction of tissues that are histologically and physiologically similar to their in vivo counterparts [91]. This method has been successfully used to reconstruct numerous human tissues such as blood vessels [91,92], bilayered skin [3], bladder [93], adipose tissue [94], heart valve [95], ureter [96], and cornea [97]. It also has been demonstrated that this technique allows to preserve subtle differences in native cells, such as receptor expression patterns, and reproduce pathologies, including psoriasis [98], fibrosis [99], amyotrophic lateral sclerosis [100], inflammation [101], and cancer [102,103].…”
Section: The Self-assembly Approach Of Tissue Engineeringmentioning
confidence: 99%